A ESCRITA DE ELIANE BRUM EM ‘MEUS DESACONTECIMENTOS – A HISTÓRIA DA MINHA VIDA COM AS PALAVRAS’ E A JORNADA PELAS MEMÓRIAS - CORDEIRO, ANY MARY OSSAK (2020)
In contemporary Brazilian literary production, autobiographical and memorialistic writing has proved to be a vigorous strategy for thinking and creating. Many writers reflect on their own experiences, contemplating both critical writing and creative writing, in which these two activities often merge into one, leaving a hybrid text to appear. It is from this perspective that the research was carried out, considering, above all, the potential of self-written and autobiographical writings. In proposing her childhood memories, journalist, writer and documentary filmmaker Eliane Brum presents a text that shares with her readers some representative scenes of the children's ethos. In the book “Meus Desacontecimento: a história da minha vida com as palavras” (2014), the writer unveils her past, and tells her life, especially her intimate relationship with the world of words. The objective of the research is to analyze data and facts that are shown as a starting point to reflect on the political and social issues they deal with, seeking more than information, the writing that weaves stories, revealing the value of each person's different life experiences , a way of reporting what is most beautiful in the hidden world: human existence. The theoretical framework used to support the work mobilizes concepts about memory, using Maurice Halbwachs (2004) and Joel Candau (2018), author who also deals with the concept of identity, to corroborate the theme will also be used Stuart Hall (2019) and Zygmunt Bauman (2005); and to deal with the writings of you we will use the contributions of Phillipe Lejeune (2008), among others.